Literature during the Pandemic: Between the Authority of Quarantine and the Freedom ofPoetry - A Reading of the Poem "The Sorrow of Minarets" by the Poet Abd al-MalikBoumanghel (مجلة إحالات, 2026)
This article explores how literature, particularly poetry, has turned its focus towards reviving humanvalues duringthe pandemics. It has not been isolated from their effects and has vividly mirrored thefundamental shifts that accompany them, thereby translating the collective concerns. The article highlights one of the contemporary poets, Algerian Abd al-Malik Boumanghel, whose verses resonated during the timeof the coronavirus. In his poem "The Sorrow of Minarets," he mourned the emptiness of mosques and the loss of their congregations. Through this, he created a creative space, blending linguistic aesthetics with thesincerity of experience, conveying poignant meanings and comprehensive descriptions that did not diminishits significance.While COVID-19 restricted the details of life and paralyzed it, poetry provided a window of hope.